A support to manage the swordfish (Xiphias gladius Linnaeus, 1758) IUUF (illegal, unreported and unregulated fishing): an easy method to identify the legal size. (19th September 2013) - Romeo, T.; Consoli, P.; Battaglia, P.; Andaloro, F.
Summary Illegal, unreported, and unregulated fishing for swordfish, mainly of immature specimens, are known to be the highest threats for this resource. This study provide a simple and useful tool for the maritime security service to recognize illegal landing sizes (<140 total length) of swordfish even when the specimens are deprived of their bills in order to elude the Italian law (Decreto del Presidente della Repubblica, 1639/68). The purpose of the present paper is to reduce the illegal swordfish fishing in the Mediterranean Sea by supplying an alternative approach to calculate the total length, starting from the lower jaw fork length (LJFL). In order to do this, the relationships of LJFL‐FL and FL‐TL of 214 specimens caught in the central Mediterranean Sea were examined by linear regression. Both linear models fit the data significantly at the P < 0.001 level. As the values of R2 were very close to 1, starting from the lower jaw‐fork length of swordfish specimens and using these equations, it is possible to estimate the value of total length with a 99% approximation.